Structure of gas turbine fuel sprays - Jasuja, A. K. (Cranfield University, 2001)
The gas turbine fuel injector hs been the focus of considerable on-going research and development for over fifty years in order to satisfy the continuously evolving requirements with regard to combustion performance, fuel consumption and pollutant emissions. This exposition attempts to summarise the principal findings on the authors own research during the past two decades, and to identify their significance within the global framework of related studies in the area of gas turbine fuel injection. His recent studies on the structure of sprays in the near-nozzle region, encompassing simplex, pressure-swirl and engine-standard, pre-filming airblast atomizers, are characterised by an unparalleled combination of near-full power air density and liquid throughput, thereby extending signicantly the knowledge database on the performance of these nozzles. They also served to reconcile the long-standing apparent contradictions in the open literature concerning the effect of ambient air pressure variation upon spray SMD for the simplex swirl injector. Moreover, they showed for the first time that the near-nozzle spray trajectory and overall mean drop size characteristics of the types of airblast nozzles used on engines are signicantly different from those of the laboratory scale atomizers featured in earlier research efforts. This is a reflection principally of the distinctive nature and scale of the fuel-air interactions involved in the two different environments. The new knowledge and understanding generated by the author's work on the plain-jet airblast concept has found practical application in large-scale industrial gas turbine engines. It is also contributing to the design of certain hybrid fuel injector congurations, which are now being offered either a an altemative to ori combination with the more established pre-filming concept. The limit of capability of both the laser sheet imaging technique developed by the author and the commercially available phase Doppler instrument have, for the first time, been successfully explored at the extreme conditions of high air density and high fuel throughputs encountered in modern gas turbines - yielding generally plausible isothermal spray property data.